Queer suspicions and the democratic cueca: art, memory and future in “Las Yeguas del Apocalipsis” (1988–1993) - Sandoval Álvarez, Juliana (Estudios de Filosofía, 2018)
This document aims to broaden the analysis of the work of the Chilean artistic duo “Las Yeguas del Apocalipsis” (formed by Pedro Lemebel and Francisco Casas), specifically in their relationship with the construction of Chile’s collective memory and future nation planning after Pinochet. Based on an approximation inspired by art sociology and in constant dialogue with central authors, this text proposes the introduction of “intersectionality” in order to further the comprehension of the strategic use made by the duo of the multiple marginal positionings they embodied. This analysis concludes that the artistic production of “Las Yeguas” concerned with “the memory question” posed a critical stance towards Chile’s past and its official instrumentalization in order to build a new future. Against this limited view, the duo proposed new memory exercises from an embodied militant difference, which aimed to include all outcasts in a truly democratic future.